2021
DOI: 10.1371/journal.pntd.0009755
|View full text |Cite
|
Sign up to set email alerts
|

A genomic snapshot of Salmonella enterica serovar Typhi in Colombia

Abstract: Little is known about the genetic diversity of Salmonella enterica serovar Typhi (S. Typhi) circulating in Latin America. It has been observed that typhoid fever is still endemic in this part of the world; however, a lack of standardized blood culture surveillance across Latin American makes estimating the true disease burden problematic. The Colombian National Health Service established a surveillance system for tracking bacterial pathogens, including S. Typhi, in 2006. Here, we characterized 77 representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Duplicate Samoan isolates were removed. Illumina reads for all clade 3.5 genomes from Colombia ( n = 20) and Chile ( n = 68) were downloaded from ENA BioProjects PRJEB42858 ( 80 ) and PRJEB20778 ( 81 ), respectively. These S. Typhi sequences from other studies and their accession numbers are listed in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Duplicate Samoan isolates were removed. Illumina reads for all clade 3.5 genomes from Colombia ( n = 20) and Chile ( n = 68) were downloaded from ENA BioProjects PRJEB42858 ( 80 ) and PRJEB20778 ( 81 ), respectively. These S. Typhi sequences from other studies and their accession numbers are listed in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Genotypes with ≥5% prevalence in the region were 3.5 (27%; n=28/105), 1.1 (18%; n=19/105), 2 (18%; n=19/105), 1.2.1 (5.7%; n=6/105), and 2.0.2 (5.7%; n=6/105). WGS data recently reported by Colombia’s Instituto Nacional de Salud ( Guevara et al, 2021 ) were not included in the regional prevalence estimates as they covered only a subset (5%) of surveillance isolates that were selected to maximise diversity, rather than to be representative. However, only four genotypes were detected in the Colombia study (1.1, 2, 2.5, 3.5), and two-thirds of isolates sequenced were genotype 2.5 (67%; n=51/77); 3.5 was also common, at 25% (n=20/77) ( Guevara et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…WGS data recently reported by Colombia’s Instituto Nacional de Salud ( Guevara et al, 2021 ) were not included in the regional prevalence estimates as they covered only a subset (5%) of surveillance isolates that were selected to maximise diversity, rather than to be representative. However, only four genotypes were detected in the Colombia study (1.1, 2, 2.5, 3.5), and two-thirds of isolates sequenced were genotype 2.5 (67%; n=51/77); 3.5 was also common, at 25% (n=20/77) ( Guevara et al, 2021 ). Similarly, all five isolates from French Guiana (sequenced via the French reference laboratory) were genotype 2.5, consistent with limited diversity and a preponderance of genotype 2.5 organisms in the north of the continent.…”
Section: Resultsmentioning
confidence: 99%
“…S . Typhi WGS data from a recent study in Colombia found genotypes 2, 2.5 and 3.5 to be the local endemic genotypes [ 42 ]. Genotype 2.5 was not detected among the Santiago isolates; however, genotype 3.5 and 2 were detected in Santiago, and were the nearest genomic neighbours of the Colombian isolates on the global tree.…”
Section: Discussionmentioning
confidence: 99%